Healthcare Chaplaincy as Specialised Spiritual Care: The Christian Call for Healing in a Global Health Context - Peng-Keller, Simon (Vandenhoeck & Ruprecht, 2024)
Is healthcare chaplaincy a health profession? This book argues that it is. It is a plea for Christian healthcare chaplaincy to be practiced as a form of specialized spiritual care, and to be understood anew within the horizon of the Christian call for healing. Only in close cooperation with other healthcare professionals, it is argued, can healthcare chaplaincy fulfil its mission and promote encompassing and evidence-based care for patients and their relatives. And only by recentering on their spiritual resources, can Christian healthcare chaplains contribute in their own unique way to healing processes and to coping with illness, dying, and grief.